ANALISIS MANAJEMEN PERSEDIAAN USAHA MIKRO KECIL DAN MENENGAH 24 ROSE PARFUME - Ertin, Muhammad Ronaldo (Journal for Management Student (JFMS), 2024)
Inventory is something that needs to be taken into account in business, this is because it allows businesses to reduce the risk of inventory shortages to meet customer demand, save costs, ensure the flow of goods, reduce delivery delays so that businesses can improve customer service. This research aims to determine the implementation of inventory management and find out how good inventory management is in 24 ROSE PARFUME MSMEs. The type of research carried out was direct observation with a qualitative approach. The source of information for this research was obtained from the perfume shop owner. The research results found that perfume shops have not implemented effective and efficient inventory management. This can be seen in the scarcity of certain variants, especially those that are best sellers. Buyers must wait for the items they need to be ordered again and then be notified again when they are available. This is because the owner will only reorder supplies when they run out. Therefore, researchers use the EOQ, Safety Stock, Reorder Point technique to look for techniques that can optimize inventory.